The Energy Sector of the Capital of Kazakhstan: Status Quo and Policy towards Smart City - Zhakiyev, Nurkhat; Kalenova, Aigerim; Khamzina, Ayagoz (International Journal of Energy Economics and Policy, 2022)
Progression in population growth of the Nur-Sultan city can lead to a load on infrastructure, energy networks, and obsolescence of planning solutions. In this light, the transition to the concept of a “Smart City” can be the best way for green urban development. This article proposes to focus on the energy system of the capital of Kazakhstan. The urgency of this study is due to the fact that currently in the research literature there is an acute lack of knowledge on the current policy of Smart City in the energy sector of Nur-Sultan. Thus, the main goal of this research paper is to identify problems in the energy system by analyzing statistical information describing the current energy system, modern urban solutions, and new approaches to urban planning based on the case study on Smart City in Kazakhstan. The article discusses the main barriers, investment policy, and necessary actions, which will allow the city to acquire the status of “Smart”. Based on the policy and measures related to energy, and economically sustainable development of the city of Nur-Sultan the regression analysis on data and SWOT analysis are implemented. The results are summarized in a table that reflects some cost analysis statistics. The results of the present study are useful to academic researchers, smart city practitioners, and policymakers.